2018
DOI: 10.2344/anpr-65-03-08
|View full text |Cite
|
Sign up to set email alerts
|

Male Gender and High Trait Anxiety Are 2 Major Factors Associated With Severe Dental Fear and Avoidance

Abstract: The purpose of this article is to investigate the association between the background characteristics of patients with severe fear of dental treatment who frequently avoid dental care and the degree of difficulty in treating them. At the time of initial presentation at a dental phobia clinic, each of 321 subjects was asked to complete the State-Trait Anxiety Inventory, the Dental Anxiety Scale, and a health questionnaire related to phobic objects. Subjects who rejected oral examination with a dental mirror were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…The proportion of those with more than 10 missed appointments was 5.9% while the proportion among boys was 9.0% and among girls 1.6%. Male sex seems to be associated with avoidance, as also seen in literature [ 30 ]. The figures for all missed appointments were higher here than for general population in the City of Oulu, Finland; 3–5% at the time of the study (Statistics, the City of Oulu Finland 2019) and among those having at least one missed appointment in line with a previous study of Tilja et al on DGA patients [ 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…The proportion of those with more than 10 missed appointments was 5.9% while the proportion among boys was 9.0% and among girls 1.6%. Male sex seems to be associated with avoidance, as also seen in literature [ 30 ]. The figures for all missed appointments were higher here than for general population in the City of Oulu, Finland; 3–5% at the time of the study (Statistics, the City of Oulu Finland 2019) and among those having at least one missed appointment in line with a previous study of Tilja et al on DGA patients [ 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…In another study, Al-Omari, et al [34] justified these results by arguing that anxiety has been shown to be positively correlated with neuroticism and women are known to generally have a higher level of neuroticism. In contrast, Yoshiaki Ihara, et al [38] reported that visiting a dentist is less common among men than women and as a result, men were classified as being severely difficult to treat in their study.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, many others did not find such relation between gender and dental anxiety [2,3,11,37]. Yoshiaki Ihara, et al [38] interestingly reported that male gender was a major factors related to past RCT experience and state anxiety (p = 0.88) as well as their number of injections (p = 0.68) (Table 1). Finally, base on the patient's answers, the most stressful part of dental procedure was drilling (37%) (Table 1).…”
Section: Gendermentioning
confidence: 95%
“…However, the number of male patients in this group was more than twice that of females. We observed that anxiety and dental phobia were more common in male patients [26].…”
Section: Discussionmentioning
confidence: 99%